Early Dutasteride Monotherapy in Patients With Elevated Serum Prostate-Specific Antigen Levels Following Robot-Assisted Radical Prostatectomy - Lu, Chin-Heng; Ou, Yen-Chuan; Huang, Li-Hua; Weng, Wei-Chun; Chang, Yu-Kang; Chen, Hung-Lin; Hsu, Chao-Yu; Tung, Min-Che (Frontiers in Oncology, 2019)
Background: To evaluate the efficacy of early dutasteride administration in patients with a detectable prostate-specific antigen (PSA) levels after robot-assisted radical prostatectomy (RARP). Methods: We retrospectively analyzed RARP patients whose pathological stage is T2a to T3b without lymph node or distant metastasis from 2007 to 2017. All patients received a daily dose of 0.5 mg of dutasteride when post-RARP PSA levels were increasing but had not achieved biochemical recurrence. PSA levels were monitored every 3 months after dutasteride administration. None of the patients received radiotherapy (RT) or androgen-deprivation therapy (ADT) before taking dutasteride. All follow-ups were begun from RARP to January 2019 or to the date of RT/ADT. Results: Thirty-five patients were included in this analysis. The median followed up was 53.6 months. Twenty-two patients (62.9%) showed a PSA response in which the PSA decreased more than 10% at the first follow-up after dutasteride administration. The Pathological stage > T2 (p = 0.012) and positive surgical margin (p = 0.046) were prognostic factors for a PSA response. Twenty-three out of 35 included patients (65.7%) did not require further RT/ADT. The significant risk factor was the PSA level (p = 0.011) at the beginning of dutasteride treatment. The cut-off value of the PSA level to avoid further RT/ADT was 0.195 ng/ml. Conclusions: Early dutasteride administration showed a significant decline in the PSA levels of patients with pathology stage >T2 and positive surgical margin in our retrospective hypothesis-generating study. If dutasteride was provided before the PSA value increased to 0.195 ng/ml after RARP, it would reduce the probability of acquirement of RT/ADT.